Phosphorylation of human placental aromatase CYP19A1. Issue 21 (11th November 2019) - Ghosh, Debashis; Egbuta, Chinaza; Kanyo, Jean E.; Lam, TuKiet T.
Abstract : Aromatase CYP19A1 catalyzes the synthesis of estrogens in endocrine, reproductive and central nervous systems. Higher levels of 17β-estradiol (E2) are associated with malignancies and diseases of the breast, ovary and endometrium, while low E2 levels increase the risk for osteoporosis, cardiovascular diseases and cognitive disorders. E2, the transcriptional activator of the estrogen receptors, is also known to be involved in non-genomic signaling as a neurotransmitter/neuromodulator, with recent evidence for rapid estrogen synthesis (RES) within the synaptic terminal. Although regulation of brain aromatase activity by phosphorylation/dephosphorylation has been suggested, it remains obscure in the endocrine and reproductive systems. RES and overabundance of estrogens could stimulate the genomic and non-genomic signaling pathways, and genotoxic effects of estrogen metabolites. Here, by utilizing biochemical, cellular, mass spectrometric, and structural data we unequivocally demonstrate phosphorylation of human placental aromatase and regulation of its activity. We report that human aromatase has multiple phosphorylation sites, some of which are consistently detectable. Phosphorylation of the residue Y361 at the reductase-coupling interface significantly elevates aromatase activity. Other sites include the active site residue S478 and several at the membrane interface. We present the evidence that two histidine residues are phosphorylated. Furthermore, oxidation of two proline residues near the active site may have implications in regulation. Taken together, the results demonstrate that aromatase activity is regulated by phosphorylation and possibly other post-translational modifications. Protein level regulation of aromatase activity not only represents a paradigm shift in estrogen-mediated biology, it could also explain unresolved clinical questions such as aromatase inhibitor resistance.